The mineralisation of dissolved organic matter recovered from temperate waterbodies during summer - Stutter, Marc I.; Cains, Jonathan (Aquatic sciences, 2016)
Natural dissolved organic matter (DOM) has many forms in freshwaters, controlling C availability for heterotrophic respiration and ecosystem functions in headwaters and downstream ecosystems. This study aimed to examine the respiration of DOM recovered using reverse osmosis (RO) during extended summer baseflow from a parkland Pond (DOM Pond ) and three headwater rivers: moorland (DOM Moor ), mixed agriculture (DOM Agr ) and predominantly moorland system with mixed riparian forest (DOM Forest ), and compared to glucose and soil-derived fulvic acid. Batch decomposition tests at time points up to 379 h were completed in a replicated 96-well micro-plate system (MicroResp) spiking river sediments carrying a standardised microbial inoculum with C sources at two concentrations (1513 and 30 µgC/g sediment dry matter). Respiration rates were greatest initially and declined over time with an exponential form. Total C respired (38–80 %, following subtraction of basal respiration controls) for the high C treatment followed: DOM Forest > DOM Agr > DOM Moor > DOM Pond > Fulvic acid. A similar order occurred at the low C treatment but BDOC >100 % was evidence that added DOM primed respiration of the sediment C above that of basal controls. Despite issues of high background salt concentrations in the DOM matrix caused by the RO procedure results show that even under summer baseflow conditions DOM can be highly labile. Labile C generated especially from agricultural catchments and those with riparian forests may be conveyed downstream to fresh and estuarine waters to control ecological processes at critical times of the year.